2018
DOI: 10.1007/s13205-018-1375-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different Agrobacterium rhizogenes strains on hairy root induction and analysis of phenolic and flavonoid compounds in marshmallow (Althaea officinalis L.)

Abstract: Hairy roots were induced in using, strains A4, A13, ATCC15834, and ATCC15834. The leaf, petiole and shoot explants of marshmallow were used for the hairy roots induction. When hairy roots appeared, cultures were established in MS (Murashige and Skoog) liquid medium without growth regulators. Hairy roots in explants appeared 5-12 days after inoculation. Maximum transformation frequency of 83% was observed on shoot explants with ATCC15834 strain. Among the strains, ATCC15834 strain showed better potential in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 35 publications
(28 reference statements)
3
18
0
Order By: Relevance
“…Observations showed that the HRs had a high rate of extensive lateral branching, the absence of geotropism and produced a greater abundance of HRs than NTRs. Similar characteristics of HRs resulting from A. rhizogenes were reported in several plants [21]. No roots or calli was observed from the explants of non-infected non-transgenic (NT) explants.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Observations showed that the HRs had a high rate of extensive lateral branching, the absence of geotropism and produced a greater abundance of HRs than NTRs. Similar characteristics of HRs resulting from A. rhizogenes were reported in several plants [21]. No roots or calli was observed from the explants of non-infected non-transgenic (NT) explants.…”
Section: Resultssupporting
confidence: 79%
“…HRs appeared at the wounding site of explants, and so, it may have been easier for A. rhizogenes to infect leaf explants, in which the wounded place is a vast area and, therefore, present the T-DNA inducing HR to the plant genome. The results achieved exhibit the same results [21]. The phloem cells, located inside the midrib region are a target of A. rhizogenes [22].…”
Section: Resultssupporting
confidence: 60%
“…HR formation in S. speciosa is genotype and bacterial strain dependent, with agropine type strains being the most virulent. Similar opine-type based differences in virulence have been observed for other plants such as Brassica oleracea, Hyoscyamus muticus, Ipomoea trichocarpa, Withania somnifera, Fagopyrum tataricum, and Althaea officinalis (Hosoki et al, 1989;Vanhala et al, 1991;Otani et al, 1996;Thilip et al, 2015;Thwe et al, 2016;Tavassoli and Safipour Afshar, 2018). Bacterial regrowth on S. speciosa leaf disk explants was most prominent for NCPPB2659, followed by Arqua1, which is in accordance with the observation that biovar 1 strains show faster exponential growth, and are more resilient to antibiotics at standard concentrations (Desmet et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…Different Agrobacterium strains, which are divergent in terms of virulence, the growth rate of transformed cells, their morphology, and secondary metabolite production, are generally employed to induce hairy roots from explants in different plant species. It has been recognized that Agrobacterium strains have different abilities to promote the production of bioactive compounds in hairy root cultures [302,320,321]. This is mainly due to the differential expression and integration of T-DNA genes into the plant genome [302,321].…”
Section: Hairy Root Culture: a Reliable Methods Of Producing Pharmaceutical Productsmentioning
confidence: 99%
“…It has been recognized that Agrobacterium strains have different abilities to promote the production of bioactive compounds in hairy root cultures [302,320,321]. This is mainly due to the differential expression and integration of T-DNA genes into the plant genome [302,321]. Therefore, the selection of an effective Agrobacterium strain for hairy root induction and secondary compound accumulation is noticeably dependent on plant species and must be empirically figured out [302,322] (Figure 5).…”
Section: Hairy Root Culture: a Reliable Methods Of Producing Pharmaceutical Productsmentioning
confidence: 99%